Effect of Pre‐Extrusion on the Microstructure and Properties of Forged Mg−Al−Zn−Ce Alloy. Issue 7 (19th May 2021) - Li, Zhu-Jin; Wang, Jin-Guo; Yan, Rui-Fang; Wang, Zheng; Ni, Tian-Yi; Sun, Hanigeer
Abstract : The effects of different morphologies of initial grains obtained by pre‐extrusion under different extrusion hole diameters or different extrusion temperatures on the microstructure and mechanical properties of forged Mg−Al−Zn−Ce alloy are studied. After homogenization treatment of as‐cast Mg−Al−Zn−Ce alloy, β‐Mg17Al12 phase is completely dissolved into the α‐Mg matrix. Then, pre‐extrusion deformation is conducted. Dynamic recrystallization (DRX) occurs during the pre‐extrusion process, and the initial grains with different grain sizes, second‐phase volume fractions, and textures are obtained. The pre‐extruded alloys show a strong basal plane (0001) texture and a monotonous increasing (or decreasing) change. After forging the pre‐extruded alloys, compared with the homogeneous forged alloy, the average grain size of the pre‐extruded‐forged (PEF) alloys is smaller and the texture strength is greatly weakened. As the microstructure of the pre‐extruded alloys, the PEF alloys show a monotonous increase (or decrease) in grain size, the volume fraction of the second phase, and texture strength. It is inferred that the microstructure and texture of PEF alloys evolve based on the microstructure and texture of the pre‐extruded alloys, and their mechanical properties are determined by the evolved microstructure and texture. Abstract : The changes of average grain size, second‐phase volume fraction, and texture strength of pre‐extruded Mg−Al−Zn−Ce alloy under different pre‐extrusion parameters are studied. The changes of average grain size, second‐phase volume fraction, and texture strength of pre‐extruded‐forged Mg−Al−Zn−Ce alloy are studied. Thus, the effect of pre‐extrusion on the microstructure and properties of forged Mg−Al−Zn−Ce alloy is revealed.